Phonological and Morphological Features of Afro-American Vernacular English (AAVE) of Malcom X Moviie - Diar Nugraha; Elisa Nurul Laili (LPPM Universitas Pekalongan, 2023)
Afro-American Vernacular English (AAVE) is one of dialects of American English and it has been extensively explored in previous research in sociolinguistic. The aims of this study are to analyze the phonological feature of AAVE based on theory by Thomas (2007) and morphological feature of AAVE based on theory by Green (2002). The movie adaption of Spike Lee entitled Malcolm X was utilized, and to obtain the data the researcher used a descriptive-qualitative approach. The result shows that the researcher found eight aspects of phonological features that include consonant aspects and eight features of morphological feature of AAVE in the movie, they are; the use of demonstrative them, copula absence, subject-verb agreement, completive done, negative forms of ain’t, negative construction, the phrase of y’all, and the phrase of ‘em, which include of three aspects of morphological features of Afro-American Vernacular English (AAVE). The most commonly used features are the deletion of -r or r-lessness such as brother and minister and the use of negator which is ain’t such as in “I ain’t no questions” for “I have no questions”. However, the researchers did not find the vowel aspect of AAVE in Malcolm X movie as described in Thomas's theory.